Expectations regarding the effectiveness of mask-wearing and pandemic fatigue: The experience in Japan - Akihiro Kawase; Mototsugu Fukushige (PLoS ONE, 2025)
Even though mask-wearing was merely “recommended” in Japan during the COVID-19 pandemic, the mask usage rate was higher than that in other countries. This study conducted an econometric analysis to examine whether expectations regarding the effectiveness of mask-wearing was a motivating factor for Japanese people to wear masks during the prolonged pandemic. The results showed that, even when considering individual factors such as risk aversion, altruism, and social pressure, the motivation of wearing a mask for self-protection had a significant positive effect. This significance was maintained even in the second year of the survey, when pandemic fatigue was occurring. This was a distinctive feature, as the effects of other individual factors on pandemic fatigue had diminished. On the other hand, the motivation for wearing a mask to protect others did not have a significant effect in either year, which contrasted with the results for self-protection. These estimation results indicate that the route of wearing a mask for self-protection was continuously effective during the prolonged pandemic, and that promoting mask-wearing through this route is effective in inducing individual behavioral changes, even during a prolonged pandemic.